FDG‐PET for preoperative evaluation of tumor invasion in ampullary cancer: A retrospective analysis. Issue 3 (12th May 2021) - Watanabe, Akira; Harimoto, Norifumi; Araki, Kenichiro; Kubo, Norio; Igarashi, Takamichi; Tsukagoshi, Mariko; Ishii, Norihiro; Hirai, Keitaro; Tanaka, Hiroshi; Mochida, Yasushi; Kogure, Norimichi; Higuchi, Tetsuya; et al.
Abstract: Background: Tumor invasion is the most significant prognostic factor in ampullary cancer and is thus a crucial factor in decision making for treatment. Endoscopic ultrasound can be performed to evaluate tumor invasion, but its diagnostic accuracy varies depending on the endoscopist. This study aimed to assess the usefulness of fluorodeoxyglucose positron emission tomography (FDG‐PET) for preoperatively predicting tumor invasion in ampullary cancer. Methods: We retrospectively evaluated 44 patients with ampullary cancer (adenoma, n  = 6; adenocarcinoma, n  = 38) who underwent surgical resection. The SUVmax of the ampullary tumor site was assessed using FDG‐PET, and the correlation among tumor invasion, lymph node metastasis, and other clinicopathological factors was evaluated. Results: The SUVmax of the ampullary tumor site gradually increased depending on the extent of tumor invasion ( p  = 0.0075). Moreover, the SUVmax was significantly different between ≤T1a and ≥T1b, which is an indication for endoscopic papillectomy or surgical resection ( p  = 0.0015). The SUVmax of the ampullary section was significantly correlated with lymph node metastasis ( p  = 0.035). Conclusion: The SUVmax of the ampullary tumor site is correlated with tumor invasion and lymph node metastasis in ampullary cancer. Thus, FDG‐PET can be a useful modality for preoperative staging and treatment strategy.